Clinicopathological characteristics of de novo and secondary myeloid sarcoma: A monocentric retrospective study. (18th April 2018) - Claerhout, Helena; Van Aelst, Sophie; Melis, Celine; Tousseyn, Thomas; Gheysens, Olivier; Vandenberghe, Peter; Dierickx, Daan; Boeckx, Nancy
Abstract: Objective: Diagnosing myeloid sarcoma remains challenging, and we aimed to provide clinicopathological features to facilitate diagnosis. Method: Clinicopathological data from 41 patients with de novo and 31 with secondary myeloid sarcoma were reviewed. Results: Most de novo cases presented with isolated myeloid sarcoma (n = 19) or myeloid sarcoma with concurrent acute myeloid leukemia (n = 15). Most secondary cases presented after acute myeloid leukemia (n = 11), myeloproliferative neoplasm (n = 9), or myelodysplastic syndrome (n = 8). Most frequent localizations were skin and lymph nodes. Immunohistochemistry showed immature and/or aberrant antigenic expression in 29% of de novo and 39% of secondary cases. Most genetic abnormalities were RUNX1‐RUNX1T1 (n = 4), CBFB‐MYH11 (n = 2), KMT2A‐MLLT3 (n = 2), and JAK2 V617F (n = 2) mutations in de novo myeloid sarcoma, and BCR‐ABL1 (n = 5) and KMT2A rearrangements (n = 2) in secondary cases. A complex karyotype was seen in 17% of de novo and 39% of secondary cases. Most prevalent treatment was induction chemotherapy followed by consolidation chemotherapy (n = 10) or allogeneic stem cell transplantation (n = 9) for de novo and radiotherapy (n = 11) for secondary cases. Conclusion: De novo myeloid sarcoma mostly presented isolated. Lesions were often localized at skin and lymph nodes. Genetic aberrations frequently involved core‐binding factor rearrangements in de novo cases and a complex karyotype in secondary cases.